2007
DOI: 10.1021/es0706899
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Seawater Flue Gas Desulfurization Process:  An Experimental Pilot Plant Study

Abstract: In previous articles by the authors on seawater S(IV) oxidation kinetics, a significant catalytic effect was demonstrated by means of a commercially available activated carbon. The aims of this study carried out at pilot plant scale were to assess the use of high-efficiency structured packing and to validate the positive results obtained previously in laboratory studies. A comparison between a packed tower and a spray column was made by maintaining the same desulfurization efficiency. A 47% reduction in seawat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…Four levels of temperature are selected in the range of 50-350 • C. The mentioned five factors with their levels are presented in Table 2. 8, 8.5, 9, 9.5 In order to increase the accuracy of the experiments design also observance of the nonlinear behavior of selected factors in the previous works (1,11), here, four levels are considered for each factor. Therefore, the conditions of sixteen tests are presented.…”
Section: The Design Of the Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four levels of temperature are selected in the range of 50-350 • C. The mentioned five factors with their levels are presented in Table 2. 8, 8.5, 9, 9.5 In order to increase the accuracy of the experiments design also observance of the nonlinear behavior of selected factors in the previous works (1,11), here, four levels are considered for each factor. Therefore, the conditions of sixteen tests are presented.…”
Section: The Design Of the Experimentsmentioning
confidence: 99%
“…They found that inorganic and organic additives could increase SO 2 removal efficiency to a certain degree. Vidal et al (1) carried out an experimental study on FGD by seawater in a catalytic packed tower in the liquid to gas ratio range of 4-15 l/m 3 . They used active carbon in packed structure and found that a 47% reduction in seawater flow rate could be obtained in a catalytic packed tower in comparison to a conventional spray tower.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, finding an effective method to reduce significantly the S-content in fuel oils is very important. In recent years, a number of technologies for flue gases desulfurization (FGD) have been developed, including wet or dry FGD processes [2][3][4][5][6]. Unfortunately, those methods have some obvious disadvantages, such as the production of a large amount of gypsum waste and waste water.…”
Section: Introductionmentioning
confidence: 99%
“…Ortez et al and Vidal et al studied oxidation kinetics of sulfur by means of a commercially available activated carbon [23,24]. The study was extended to a pilot scale unit to demonstrate the high-effi ciency of structured packing, which reduced the seawater fl ow rate by 47% and the production cost by 33%.…”
Section: Introductionmentioning
confidence: 99%